Peran Kelompok Masyarakat dalam Rehabilitasi Ekosistem Mangrove di Pesisir Kota Semarang - Nana Kariada Tri Martuti; Sri Mulyani Endang Susilowati; Wahid Akhsin Budi Nur Sidiq; Ditha Prasisca Mutiatari (Jurnal Wilayah dan Lingkungan, 2018)
The coastal area of Semarang City has a strategic function for regional economic development. Due to land use change, the environmental quality of coastal area is damaged and declining. The environmental quality decline has affected the socio-economic quality of local community. This research aims to investigate the role of local community in sustainable environmental management in Semarang City coastal area. The study takes place in two kelurahans, namely Tugurejo and Mangunharjo, and applies a descriptive qualitative approach to figure out the local community role in the coastal environment rehabilitation. Data collection through a preliminary survey supported with a satellite imagery study covers up an appropriate ecosystem with the research substance. Then the following data analysis and interpretation uses Miles and Huberman interactive analysis method. The results show the significant role of the local community in coastal area quality management and improvement in Semarang City more effectively and efficiently. This relates to their active interactions in various community-based programs including wave-breaking instrument building and mangrove nursery and planting.